Indonesia Modifikasi Labu Kuning (Curcubita moschata) pada Permen Gummy Jelly sebagai Camilan Tinggi Vitamin A untuk Anak Stunting: Modifikasi Labu Kuning (Curcubita moschata) pada Permen Gummy Jelly sebagai Camilan Tinggi Protein dan Vitamin A untuk Anak Stunting - Robi'atun Wulandari Sa'adah; Sinta Silvia (Amerta Nutrition, 2022)
Background: Pumpkin is one food source of vitamin A. Pumpkin can be processed into gummy jelly as a snack that has a high vitamin A content. Objectives: This study aims to determine and analyze acceptability, protein and vitamin A levels in gummy jelly candy with modified pumpkin as a high-vitamin A snack to help improve stunting children's nutrition at school age. Methods: This research is a pure experimental research with a Completely Randomized Design (CRD). The number of formulas tested were 3 formulas with 3 repetitions, namely F0 (0 g pumpkin), F1 (80 g pumpkin consisting of 30 g pumpkin extract and 50 g pumpkin puree), and F2 (160 g pumpkin consisting of 60 g of pumpkin essence and 100 g of pumpkin puree). There were 15 panelists in this study consisting of 3 trained panelists and 12 semi-trained panelists. Results: Based on the hedonic test results, it was found that F1 (30 g pumpkin extract and 50 g pumpkin puree) was the panelist's most preferred formula. The content of protein and vitamin A in candy per serving size (40 g) is 20.5 g and 37.75 mcg. There was a significant difference in taste characteristics between F0 and F2 (p=0.033) and between F1 and F2 (p=0.007). While on the characteristics of consistency, aroma, and color there is no significant difference. Conclusions: The formula with the highest acceptance is F1. Per two serving of candy (40 g) can meet 10-15% of protein and vitamin A needs in children aged 7-12 years.